The solutions Degenerate Elliptic-Parabolic Equations - Gadjiev, Tahir; Kerimova, M.N. (JOURNAL OF ADVANCES IN MATHEMATICS, 2013)
We prove some a priori estimates of solutions for degenerate elliptic-parabolic equations.